A novel benzamide derivative SY-15 inhibits multiple myeloma cell proliferation (Annals of Medical Research, 2025)
Aim: Over the past two decades, the natural course of multiple myeloma (MM) has changed significantly, primarily due to the emergence of novel therapeutic agents targeting the bone marrow microenvironment (BMM). Despite these advancements, the underlying mechanisms of drug resistance remain largely unclear. In this study, the effects of a novel benzamide derivative, SY-15, on MM cell lines were investigated, and the findings suggest that this molecule could be a promising anticancer drug candidate, warranting further research.Materials and Methods: Multiple myeloma (MM) cell lines (MM1S, U266, H929, RPMI8226) were cultured, and the effects of various concentrations of a novel benzamide derivative on cell viability were evaluated using the MTT assay. Results: The anticancer activity of the SY-15 molecule was evaluated in multiple myeloma (MM) cell lines following 72 hours of treatment, and for comparison, in the L929 normal fibroblast cell line. A statistically significant difference in cell viability percentages was observed among the five cell lines (p